Fast mineralization and detoxification of amoxicillin and diclofenac by photocatalytic ozonation and application to an urban wastewater
The degradation of two organic pollutants (amoxicillin and diclofenac) in 0.1 mM aqueous solutions was studied by using advanced oxidation processes, namely ozonation, photolysis, photolytic ozonation, photocatalysis and photocatalytic ozonation. Diclofenac was degraded quickly under direct photolysis by artificial light (medium-pressure vapor arc, lambda(exc) > 300 nm), while amoxicillin remained very stable. In the presence of ozone, regardless of the type of process, complete degradation of both organic pollutants was observed in less than 20 min. Photolysis or ozonation on their own led to modest values of total organic carbon (TOC) removal (<6% or 41%, respectively in 180 min), while for photocatalysis (no ozone present) a significant fraction of nonoxidizable compounds remained in the treated water (similar to 15% after 180 min). In the case of photolytic ozonation, the kinetics of TOC removal was slow. In contrast, a relatively fast and complete mineralization of amoxicillin and diclofenac (30 and 120 min, respectively) was achieved when applying the photocatalytic ozonation process. The absence of toxicity of the treated waters was confirmed by growth inhibition assays using two different microorganisms, Escherichia coli and Staphylococcus aureus. Photocatalytic ozonation was also applied to an urban wastewater spiked with both amoxicillin and diclofenac. The parent pollutants were easily oxidized, but the TOC removal was only as much as 68%, mainly due to the persistent presence of oxamic acid in the treated sample. The same treatment allowed the effective degradation of a wide group of micropollutants (pesticides, pharmaceuticals, hormones and an industrial compound) detected in non-spiked urban wastewater.